AHA: AI-guided tool for the quantification of venom-induced haemorrhage in mice - Jenkins, Timothy P.; Laprade, William Michael; Sánchez, Andrés; Tulika, Tulika; O’Brien, Carol; Sørensen, Christoffer V.; Stewart, Trenton K.; Fryer, Thomas; Laustsen, Andreas H.; Gutiérrez, José María (Frontiers in Tropical Diseases, 2022)
Venom-induced haemorrhage constitutes a severe pathology in snakebite envenomings, especially those inflicted by viperid species. To both explore venom activity accurately and evaluate the efficacy of viperid antivenoms for the neutralisation of haemorrhagic activity it is essential to have available a precise, quantitative tool for empirically determining venom-induced haemorrhage. Thus, we have built on our prior approach and developed a new AI-guided tool (AHA) for the quantification of venom-induced haemorrhage in mice. Using a smartphone, it takes less than a minute to take a photo, upload the image, and receive accurate information on the magnitude of a venom-induced haemorrhagic lesion in mice. This substantially decreases analysis time, reduces human error, and does not require expert haemorrhage analysis skills. Furthermore, its open access web-based graphical user interface makes it easy to use and implement in laboratories across the globe. Together, this will reduce the resources required to preclinically assess and control the quality of antivenoms, whilst also expediting the profiling of haemorrhagic activity in venoms for the wider toxinology community.